Autochthonous Fermentation as a Means to Improve the Bioaccessibility and Antioxidant Activity of Proteins and Phenolic Compounds of Yellow Pea Flour - Cipollone, María Agustina (2024)
This study focused on evaluating the potential of natural fermentation of pea flour to improve the release of antioxidant compounds. Preliminary fermentations of 36.4 % w/w flour dispersions were performed in tube under different conditions (24 and 48 h, 30 and 37°C). Finally, fermented flours (FF) were obtained in a bioreactor under two conditions: 1: 36.4% w/w, 24 h, 30°C (FF1); 2: 14.3% w/w, 24 h, 37°C (FF2). pH values decreased to 4.4-4.7, with a predominance of lactic acid bacteria. As in the fermentations in tube, an increment of the proteolysis degree (TNBS method) (greater for FF2), polypeptides aggregation and decrease of solubility, increase of <2 kDa peptides, and increase in the Oxygen Radical Absorption Capacity (ORAC) potency of PBS-soluble fractions after fermentation was demonstrated. Also, fermentation increased the proteolysis degree after simulated gastrointestinal digestion (SGID, COST-INFOGEST) respect to the non-fermented flour digests, with some differences in the molecular composition of the different digests. ORAC and Hydroxyl Radical Averting Capacity (HORAC) potencies increased in all cases. The digest of FF2 (FF2D) presented the greater ORAC value, with higher activities for >4 kDa, some in the range 2-0.3 kDa and <0.10 kDa fractions. Fermentation also increased the 60% ethanol extracted phenolic compounds, mainly flavonoids, and the ORAC activity. After SGID, the flavan-3-ols disappeared but some phenolic acids increased respect to the flour. Fermentation in condition 2 was consid-ered the most appropriate to obtain a functional antioxidant ingredient.